2010
DOI: 10.1039/c0ob00064g
|View full text |Cite
|
Sign up to set email alerts
|

The gas phase Smiles rearrangement of anions PhO(CH2)nO− (n = 2–4). A joint theoretical and experimental approach

Abstract: A combination of experimental data [using (18)O labelling fragmentation data together with metastable ion studies in a reverse sector mass spectrometer (from a previous study)] and ab initio reaction coordinate studies at the CCSD(T)/6-31++G(d,p)//B3LYP/6-31++G(d,p) level of theory, have provided the following data concerning the formation of PhO(-) in the gas-phase from energized systems PhO(CH(2))(n)O(-) (n = 2-4). All DeltaG values were calculated at 298 K. (1) PhO(CH(2))(2)O(-) effects an ipso Smiles rearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Starting with the plain phenol (11), we found that the spiro was a TS with a relative energy of 28.8 kcal mol À1 , a similar magnitude was reported in the literature. [29] This high energy barrier is consistent with the fact that the reaction experimentally fails. [27] Similar results were obtained when considering the 2-chloro and 2methoxyphenols (12) and (13): the energies of the corresponding spiro transition states were 26.6 and 29.2 kcal mol À1 , respectively ( Table 2), and the reactions fail.…”
Section: Resultssupporting
confidence: 74%
“…Starting with the plain phenol (11), we found that the spiro was a TS with a relative energy of 28.8 kcal mol À1 , a similar magnitude was reported in the literature. [29] This high energy barrier is consistent with the fact that the reaction experimentally fails. [27] Similar results were obtained when considering the 2-chloro and 2methoxyphenols (12) and (13): the energies of the corresponding spiro transition states were 26.6 and 29.2 kcal mol À1 , respectively ( Table 2), and the reactions fail.…”
Section: Resultssupporting
confidence: 74%
“…In contrast to studies on the solution phase, gas‐phase Smiles rearrangement reactions can occur upon collisional activation, even without the activation of the aromatic ring by electron‐withdrawing groups. For example, the product ion PhO – obtained in the fragmentation of PhO(CH 2 ) 2 O − was generated exclusively via the Smiles rearrangement, which was confirmed by heavy atom ( 13 C and 18 O) labeling study and validated by theoretical calculation . In the fragmentations of deprotonated 2‐(4,6‐dimethoxypyrimidin‐2‐ylsulfanyl)‐ N ‐phenylbenzamide and sulfonylurea herbicides, gas‐phase Smiles rearrangements have also been proposed …”
Section: Methodsmentioning
confidence: 60%
“…For example, the product ion PhOobtained in the fragmentation of PhO(CH 2 ) 2 O À was generated exclusively via the Smiles rearrangement, which was confirmed by heavy atom ( 13 C and 18 O) labeling study and validated by theoretical calculation. [9,10] In the fragmentations of deprotonated 2-(4,6dimethoxypyrimidin-2-ylsulfanyl)-N-phenylbenzamide and sulfonylurea herbicides, gas-phase Smiles rearrangements have also been proposed. [11,12] Amide compounds are pervasive in nature and have been extensively studied by mass spectrometry.…”
mentioning
confidence: 99%
“…[38][39][40] Several other common fragmentations were also observed, such as the ion at m/z 256 that results from the loss of H 2 O, and the benzyl anion at m/z 91 that results from the direct decomposition of A-1. Such cases are not unusual in the gas-phase anionic fragmentations.…”
Section: Resultsmentioning
confidence: 96%